Analisis Pengaruh Kepribadian Ekstroversi, Locus of Control dan Kecerdasan Emosional Terhadap Kinerja Perilaku Petugas Tiket Bus Trans Semarang dengan Dukungan Sosial Sebagai Variabel Moderasi - Annisa Sabila; Hardani Widhiastuti; Rusmalia Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of extraversion personality, locus of control, and emotional intelligence on the behavioral performance of Trans Semarang bus ticket officers, with social support as a mediating variable. This research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (SmartPLS 4.0). The validity test results indicate that all indicators have outer loading values greater than 0.70 and AVE values above 0.50. In addition, composite reliability and Cronbach’s alpha values exceed 0.70, confirming that the research instruments are valid and reliable. The discriminant validity test using HTMT values below 0.90 also demonstrates good construct validity. The structural model results show that the R-square values are 0.866 for behavioral performance and 0.749 for social support, indicating strong predictive power. Hypothesis testing reveals that extraversion, locus of control, and emotional intelligence have a positive and significant effect on both behavioral performance and social support (p < 0.05). Social support also has a significant positive effect on behavioral performance.Furthermore, social support is proven to act as a partial mediator in the relationship between the independent variables and behavioral performance. This study highlights the importance of personality traits and emotional intelligence, supported by social factors, in enhancing employees’ behavioral performance.